America$1 (Bs Mark Twain.s With illus. by Lynd Ward. - McNeer, May Yonge, 1902-; Ward, Lynd, 1905-1985. (Boston, Houghton Mifflin, 1962)
A biography of the American author known for his humanity as well as his wit.
Keywords: Twain, Mark, -- 1835-1910 -- Juvenile literature; Twain, Mark, -- 1835-1910.; Authors, American -- 19th century -- Biography -- Juvenile literature; Humorists, American -- 19th century -- Biography -- Juvenile literature; Authors, American; Humorists